Предмет: Алгебра,
автор: zhenya1migd
спростіть вираз (а+6/а^2-4 - 2/а^2+2а): а+2/а^2-2а
Ответы
Автор ответа:
0
1) (a+6)/(a-2)(a+2) -2/a(a+2) =(a(a+6) -2(a-2)) /a(a-2)(a+2) =(a² +6a -2a+4) /a(a-2)(a+2) =(a² +4a +4) /a(a-2)(a+2) =(a+2)² /a(a-2)(a+2) =(a+2) /a(a-2)
2) (a +2)/(a² -2a) : (a+2)/(a² -2a) =(a+2)*(a² -2a) /(a² -2a)*(a+2) =1
2) (a +2)/(a² -2a) : (a+2)/(a² -2a) =(a+2)*(a² -2a) /(a² -2a)*(a+2) =1
Автор ответа:
0
при делении дробь переворачиваем и будет умножение :(a+2)/(a²-2a) = *(a²-2a)/(a+2)
Похожие вопросы
Предмет: Русский язык,
автор: selcanseyidmammedli
Предмет: Английский язык,
автор: tommkepeesher
Предмет: Математика,
автор: nastyi299
Предмет: История,
автор: mkhit
Предмет: Математика,
автор: svetlanazimina8